2017
DOI: 10.13187/ejced.2017.4.645
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Metacognitive Reading Strategies among students at International Burch University: A Case Study

Abstract: Being notably absent from many classrooms and largely unaware of by many language learners, metacognitive reading strategies have attracted a keen interest of scholars and have been extensively researched in very diverse contexts. Thus, the primary goal of this research is to determine the overall usage of different types of metacognitive reading strategies by non-native English language speakers at International Burch University. For that purpose, the Metacognitive Reading Strategies Questionnaire (MRSQ) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 7 publications
(19 reference statements)
4
13
3
Order By: Relevance
“…Still, in the aforementioned studies, males were reported to be more frequent strategy users than females, which was not substantiated by the current findings indicating a higher strategy usage by females than males, similar to Doró and Habók (2013), Goh and Foong (1997) and Green and Oxford (1995). The current study's results are not aligned with the research findings of some other studies conducted in the same socio-cultural context (Bećirović, et al, 2017, Mašić et al, 2020, which pointed to significant differences in strategy use.However, the EXPLORING THE RELATIONSHIP BETWEEN LANGUAGE LEARNING STRATEGIES results are in line with Bećirović (2017), whose study showed no significant influence of gender on students' achievement in EFL learning, and Rizvić and Bećirović (2017), who identified no significant differences between female and male learners regarding their willingness to communicate in English as a foreign language.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Still, in the aforementioned studies, males were reported to be more frequent strategy users than females, which was not substantiated by the current findings indicating a higher strategy usage by females than males, similar to Doró and Habók (2013), Goh and Foong (1997) and Green and Oxford (1995). The current study's results are not aligned with the research findings of some other studies conducted in the same socio-cultural context (Bećirović, et al, 2017, Mašić et al, 2020, which pointed to significant differences in strategy use.However, the EXPLORING THE RELATIONSHIP BETWEEN LANGUAGE LEARNING STRATEGIES results are in line with Bećirović (2017), whose study showed no significant influence of gender on students' achievement in EFL learning, and Rizvić and Bećirović (2017), who identified no significant differences between female and male learners regarding their willingness to communicate in English as a foreign language.…”
Section: Discussioncontrasting
confidence: 99%
“…Variations in the application of all or some strategy subtypes at different grade levels was observed and measured as significant in other studies (Bećirović et al, 2017;Brdarević-Čeljo & Asotić, 2017;Chen, 2009;2014;Gavriilidou & Petrogiannis, 2016;Habók & Magyar, 2018;Magogwe & Oliver, 2007;Mitits et al, 2016), which is not aligned with the current study's findings, which even suggested that high school seniors reported the same or lower strategy use. This discordance with the stated results was slightly unanticipated as four years in the period of adolescence is a rather lengthy timeframe for students' cognitive and emotional development and increased self-awareness, and is expected to produce an increase in strategy awareness.…”
Section: Discussioncontrasting
confidence: 94%
“…On the other hand, nationality proved to be a significant factor in cross-cultural sensitivity and intercultural effectiveness (Bećirović, Brdarević Čeljo, 2018;Bećirović et al, 2019). In these studies, Bosnian students achieved better results both in measuring metacognitive strategy awareness, on the one hand, and cultural sensitivity and intercultural effectiveness, on the other hand, than Turkish students (Bećirović et al, 2017, Bećirović, Brdarević Čeljo, 2018and Bećirović et al, 2019, but the difference is significant only when their cross-cultural sensitivity and intercultural effectiveness are measured. The conclusions that can be drawn from the aforementioned and are not in concordance with some previous findings (Rear, 2017;Roksa et al, 2017;etc.…”
Section: Discussionmentioning
confidence: 88%
“…When the results of the current study are compared to the results of other studies conducted in the Bosnian context among Bosnian and Turkish participants studying at international universities in Bosnia and Herzegovina, some interesting conclusions can be drawn. Namely, investigating metacognitive strategy awareness of Bosnian university-level students of different nationalities, namely Bosnian, Turkish and others, both Bećirović, Brdarević Čeljo and Dubravac (2018) and Bećirović, Brdarević Čeljo and Sinanović (2017) found that the impact of nationality on the use of metacognitive strategies was insignificant. On the other hand, nationality proved to be a significant factor in cross-cultural sensitivity and intercultural effectiveness (Bećirović, Brdarević Čeljo, 2018;Bećirović et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Gender-based differences have attracted a keen interest of many scholars exploring reading strategy use (Abu-Rabia, 1999;Bugel & Buunk, 1996;Chavez, 2001;Green & Oxford, 1995;Kaylani, 1996;Mayer, 1996;Sheorey, 1999;Sheorey & Mokhtari, 2001). In general, most research results have demonstrated that females use reading strategies more frequently than males (Bećirović, Brdarević-Čeljo, & Sinanović, 2017;Dreyer & Oxford, 1996;Green & Oxford, 1995;Kaylani, 1996;Oxford & Nyikos, 1989;Phakiti, 2003;Sheorey, 1999), although, similarly to the other variables explored, some results have revealed quite the opposite (Baily, 1996). Furthermore, the dominance of males in the use of some strategies and females in the use of others was also observed (Brdarević-Čeljo & Asotić, 2017; Goh & Fong, 1997;Lee, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%